GEs ecomagination Challenge : an experiment in open innovation - Chesbrough, Henry William (London : SAGE Publications Ltd, 2017)
The GE ecomagination Challenge case study takes place in 2010 when Beth Comstock, chief marketing officer and senior vice president of General Electric is planning a meeting with GE's CEO, Jeffrey Immelt. The pair plan to discuss the company's ecomagination Challenge, an open innovation process that solicited energy ideas from individuals and start-ups to identify potential ventures for in green and renewable energy areas for GE to invest in. Pursuing this approach required several organizational processes that were new to GE. For one, they chose to partner with four outside VC firms, and pool the due diligence process with them and co-invest with them. For another, they chose to receive submissions to the ecomagination Challenge through a publicly available website. Nearly 4,000 submissions were received, and 75,000 people participated in the process. By 2011, the ecomagination Challenge had already resulted in $140 million (out of its allocated $200 million) of investments in 23 ventures. However, the scale of these results was dwarfed by GE's $37 billion energy business. And it would take years for these young ventures to reach a size that would be of direct business value to GEs energy business. And of course many of the young ventures would likely fail along the way. So the time has come in the setting of the case for Comstock to evaluate the results of the ecomagination Challenge more carefully, and decide on whether and how to continue this kind of activity within GEs energy business, or in other GE businesses. How should GE measure ecomagination's results in order to justify its existence and possible future investments? What new processes and structures would be required to make sure that some of the Challenges investments would pay off for GE down the road? Based on the programs results to date, was the program a good investment for GE and something GE should repeat, or was it a noble experiment that should be discontinued?
Originally published in Chesbrough, H. (2012). GEs ecomagination challenge: An experiment in open innovation. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; General Electric Company; Technological innovations -- Case studies; Leadership -- Case studies